The Flowering Season-Meter at FLOWERING LOCUS C Across Life Histories in Crucifers - Buzas, Diana Mihaela; Nishio, Haruki; Kudoh, Hiroshi (Frontiers in Plant Science, 2021)
Many plant species overwinter before they flower. Transition to flowering is aligned to the seasonal transition as a response to the prolonged cold in winter by a process called vernalization. Multiple well-documented vernalization properties in crucifer species with diverse life histories derive from environmental regulation of a central inhibitor of flowering gene, Flowering Locus C (FLC). Episode (s) of flowering are prevented while FLC expression is high and enabled while FLC expression is low. FLC repression outlasts the winter to coincide with spring; this heterochronic aspect is termed “winter memory”. In the annual Arabidopsis thaliana, winter memory has long been associated with the highly conserved histone modifiers Polycomb and Trithorax, which have antagonistic roles in transcription. However, there are experimental limitations in determining how dynamic, heterogenous histone modifications within the FLC locus generate the final transcriptional output. Recent theoretical considerations on cell-to-cell variability in gene expression and histone modifications generating bistable states brought support to the hypothesis of chromatin-encoded memory, as with other experimental systems in eukaryotes. Furthermore, these advances unify multiple properties of vernalization, not only the winter memory. Similarly, in the perennial Arabidopsis halleri subsp. gemmifera, recent integration of molecular with mathematical and ecological unify FLC chromatin features with the all-year-round memory of seasonal temperature. We develop the concept of FLC season-meter to combine existing information from the contrasting annual/perennial and experimental/theoretical sectors into a transitional framework. We highlight simplicity, high conservation and discrete differences across extreme life histories in crucifers.